Corporate Governance dan Kinerja Keuangan Bank di Indonesia: Sebelum dan Selama Covid-19 - Sudradjat Sudradjat; Muhamad Umar Mai; Djoni Djatnika (Program Studi Akuntansi FPEB UPI, 2023)
This research has two objectives. First, compare the financial performance of banks as measured by Return on assets (ROA) and Return on equity (ROE) between before and during Covid-19. Second, examine the effect of corporate governance on ROA and ROE, before and during Covid-19. The research was conducted in the Indonesian capital market during the period 2014-2021. The data analysis method used the Wilcoxon signed rank test for the first objective, and panel data regression for the second purpose. The results of the analysis show that: ROA and ROE during Covid-19 are significantly smaller than ROA and ROE before Covid-19; The most important components of corporate governance in increasing the ROA and ROE of the banking sector in the Indonesian capital market are the size of the board of directors and the age of the president director.